Banking consolidation and small businessfinance: empirical evidence for Germany - Katharina Marsch; Christian Schmieder; Katrin Forster-van Aerssen (Deutsche Bundesbank, 2007)
Since the early 1990s an unprecedented process of consolidation has taken place in the banking sector in most industrialised countries raising concern of policymakers that it may reduce access to credit for the small business sector. While most of the existing empirical studies have focused on the U.S., this paper is the first one empirically investigating the effects of banking consolidation in Germany. As small and medium sized German companies traditionally almost exclusively rely on bank credit and as they represent the vast majority of the corporate sector reduced credit availability for those companies could particularly endanger economic growth. Based on an exceptional panel dataset comprising merged data of the German credit register and balance sheet data of German firms and banks we find - contrary to public fear - that the ongoing banking consolidation in Germany does not have a significant negative impact on the financing of small and medium-sized enterprises (SME). We measure the financing opportunities of SMEs based on the bank debt/assets ratio and the logarithmized credit size and control both explicitly for bank mergers and for the increase in the average bank size in the course of the consolidation process. In addition, we observe that the concentration in the banking market is insignificant for SME financing and that there is no significant difference between commercial banks, savings banks and private banks.
Keywords: G21; G2; G1; 330; Banking consolidation; bank mergers; SME financing; Bank; Wirtschaftskonzentration; Klein- und Mittelunternehmen; Finanzierung; Kreditrationierung; Schätzung; Deutschland